Investigation of the mechanical behavior and atomic deformation mechanisms of high-entropy CoCrCuFeNi alloy under tensile and compressive strain rates: a molecular dynamics study - Kazanc, Sefa; Baykara, Oktay (Springer Heidelberg, 2026)
High-entropy alloys (HEAs) are attracting considerable interest in advanced technology fields due to their potentially superior mechanical properties, excellent thermal stability, and high corrosion resistance compared to conventional materials. Multicomponent systems, particularly alloys like CoCrCuFeNi, exhibit remarkable mechanical performance due to their complex atomic arrangement and multiple deformation mechanisms. In this study, the changes in the mechanical and microstructural properties of CoCrCuFeNi HEA as a result of tensile and compressive deformation applied at different strain rates were investigated using Molecular Dynamics (MD) simulation. The potential of the Embedded Atom Method (EAM) has been used in modeling interatomic interactions. The results were evaluated in terms of Young's modulus, yield stress, dislocation density, build-up defects, and atomic configurations. The results show that the yield stress increases as the strain rate increases. It has been observed that the Young's modulus calculated in the elastic regime during tensile and compressive deformation processes remains largely independent of the strain rate. Furthermore, it was observed that dislocation density increased at low strain rates, while it decreased at high strain rates. Increased yield stress and strain rate sensitivity (SRS) indicate a change in the dominant deformation mechanisms. These findings demonstrate that HEAs can exhibit exceptional mechanical strength even at high strain rates, and therefore offer fundamental mechanical insights into deformation behavior under high strain rates. This study serves as an important reference for theoretical and computational research aimed at understanding the plastic deformation mechanisms of HEAs.
Keywords: Molecular dynamics; High-entropy alloy; Strain rate; Tension-compression